The importance of socioeconomic position in smoking, cessation and environmental tobacco smoke exposure during pregnancy - Madureira, Joana (Sci Rep, 2020)
Tobacco is still a leading cause of premature death and morbidity. Particular attention has been given to pregnant women due to the scientific evidence on the importance of early life exposures for disease onset later in life. The purpose of this study was to assess smoking prevalence, smoking cessation rate and environmental tobacco smoke (ETS) exposure, and the role of socioeconomic position (SEP) on these behaviors among pregnant women. Cross-sectional data of 619 pregnant women, aged between 18 and 46 years, from Porto Metropolitan Area, Portugal, on current smoking, ETS exposure and SEP indicators was collected, face-to-face, using a questionnaire filled in during a personal interview at the postpartum hospital stay. The smoking prevalence, and ETS exposure among non-smokers before pregnancy was 27.6% and 57.4%, respectively. 4.1% of the participants reported to have stopped smoking before pregnancy, whereas about 41% quitted along pregnancy, resulting in a smoking prevalence at birth of 14.6%. Exposure to ETS also decreased throughout pregnancy to 49.8% at birth. Lower educational level was significantly associated with both higher smoking prevalence and exposure to ETS and lower smoking cessation. This study demonstrates that smoking and ETS exposure during pregnancy remains high, and that there are still significant socioeconomic inequalities in smoking; thus tobacco-focused preventive interventions need to be reinforced.